Żydowska pisarka z Breslau i jej kontrowersyjny mistrz: Else Croner i Eduard Spranger – życie i twórczość w czasach narodowego socjalizmu z perspektywy badań biograficznych - Filipowska, Marta (2024)
The following article presents a summary of Polish and German scientific research on the life and work of a German writer of Jewish origin associated with Berlin and Breslau, Else Croner, and her mentor and guide in the field of pedagogical sciences, Eduard Spranger. The paper investigates the direct influence of National Socialism on Else Croner and Eduard Spranger's works, and reveals previously unknown facts shedding new light on the figure of Eduard Spranger and his views.
Keywords: Croner, Else; Spranger, Edurad